HUBUNGAN KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KEPUASAN KERJA PEGAWAI DI KPU KOTA KEDIRI - Riduwan Riduwan (Universitas Islam Kadiri, 2020)
Presence rate of several staff at KPU Kota Kediri is considered in a low level. In addition, there were some staff who proposed mutation to other institution, low work loads, low work motivation, leadership dualism at the office of KPU Kota Kediri. Such phenomena showed that the office suffered from low satistaction rate. While many factors affect work satisfaction rate of the staff, this study focused on only three of them: leadership, work environment, and motivation. From this standpoint, there came statement of the problem: Was there any relationship of leadership, work environment, and motivation to work satisfaction of the staff at KPU Kota Kediri. Method used in the study was an explanatory study using population obtained from KPU Kota Kediri staff. There were 21 staff subject to a sensus sampling. Technique of data collection used questioner and documentary techniques with instrument of questioner and Likert Scale for measurement. Data collected were analysed by Rank Kendall correlation. The study resulted in as follows:1. Leadership had a positive relationship with work satisfaction of the staff at KPU Kota Kediri.2. Work environment had a positive relationship with work satisfaction of the staff at KPU Kota Kediri and Motivation had a positive relationship with work satisfaction of the staff at KPU Kota Kediri. 3. The simultaneous of leadership, work environment and motivation on work satisfaction of the staff at KPU Kota Kediri was 88%. The other 12% effect was derived from other variables than leadership, work environment, and motivation. In conclusion, superiors of KPU Kota Kediri could enhance work satisfaction of the staff by means of improving their leadership, work environment, and motivation, either partially or simultaneously.